Self-Regulation Shift Theory: A Dynamic Personal Agency Approach to Recovery Capital and Methodological Suggestions - Benight, Charles C.; Harwell, Aaron; Shoji, Kotaro (Frontiers in Psychology, 2018)
Abstract Recovery capital highlights person and environmental resources associated with overcoming significant life challenges. This paper utilizes social cognitive theory as a framework for understanding how recovery capital functions in trauma adaptation. This theory outlines the bidirectional, dynamic interactions among person (e.g., cognitive and affective), behavioral (e.g., problem focused coping), and environmental variables (i.e., triadic reciprocal determinism). The value of this approach to understanding human adaptation to trauma is that it targets the self-regulatory processes that unfold for trauma survivors as they attempt to put their lives back together. Self-regulation shift theory, as an extension to social cognitive theory, is offered to explain how self-regulation is involved in both positive and negative adjustment. The theory uses a dynamical systems approach and highlights the mechanisms related to nonlinear shifts in both positive and negative trauma recovery. According to self-regulation shift theory, trauma recovery may not be linear with threshold shifts (i.e., bifurcations) from one organized state (broken self) to another (empowered self). Coping self-efficacy perceptions are a critical factor influencing these threshold shifts. This paper concludes with a brief review of study designs and analytic procedures that can facilitate the application of nonlinear dynamic research in this area.